Comprehensive Survey of Clinical Trials Registration for Melanoma Immunotherapy in the ClinicalTrials.gov - Wang, Yan-Bo; Lv, Gang; Xu, Feng-Hua; Ma, Lin-Lu; Yao, Yong-Ming (Frontiers in Pharmacology, 2020)
Objective: To evaluate of immunotherapeutic clinical trials comprehensively can provide reference for melanoma treatment and research. Methods: The ClinicalTrials.gov web site was used to retrieve and download all registered clinical trials for melanoma immunotherapy on August 1 (updated on August 25). All registration trials that met the inclusion criteria were collected regardless of the type of study, the status of recruitment, and the results of the study. The general characteristics, methodological characteristics, and the types of immunotherapeutic drugs included of these trials were analyzed. Results: Finally, 242 eligible trials were included and evaluated. Of them, 30.58% were completed, 16.94% were terminated and two were withdrawn; 77.69% recruited less than 100 participants; 30.47% were randomized; 45.49% was single group assignment; 88.84 % were not masked; the primary purpose was treatment; 44.21% had data on monitoring committees; 27.69% used US FDA-regulated immunization drugs; 78.51% without results posted; 42.98% were sponsored by the industry. Immunological checkpoint inhibitors is most often studied, with 53.55% of the trials involving PD-1, the most commonly studied was Nivolumab. Conclusions: Currently, most of the registered clinical trials are interventional trials and focused on adults. A lot of studies is underway, and as the research progresses, melanoma patients will have the opportunity to introduce more effective and safe treatments.